2003
DOI: 10.1093/humrep/deg336
|View full text |Cite
|
Sign up to set email alerts
|

A comparative randomized multicentric study comparing the step-up versus step-down protocol in polycystic ovary syndrome

Abstract: The step-up protocol using rFSH (Puregon), is more efficient in obtaining a monofollicular development and ovulation than the step-down protocol, in women with CC-resistant polycystic ovaries. Although the duration of stimulation is longer, the rate of ovarian hyperstimulation is much lower using the step-up protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 21 publications
1
55
0
8
Order By: Relevance
“…24 Previous studies that assessed follitropin-alfa for ovulation induction in women with CC resistant PCOS, have reported that the pregnancy rate per stimulated cycle was approximately 18-20%. 8,[25][26][27] However, the current trial revealed comparable biochemical and clinical pregnancy rates (21% and 19% respectively) upon using CC for 10 days in ovulation induction for CC resistant Patients. Furthermore, our data emphasized that the pregnancy rates of CC 10 day protocol were similar to follitropin-alfa therapy.…”
Section: Discussionmentioning
confidence: 51%
“…24 Previous studies that assessed follitropin-alfa for ovulation induction in women with CC resistant PCOS, have reported that the pregnancy rate per stimulated cycle was approximately 18-20%. 8,[25][26][27] However, the current trial revealed comparable biochemical and clinical pregnancy rates (21% and 19% respectively) upon using CC for 10 days in ovulation induction for CC resistant Patients. Furthermore, our data emphasized that the pregnancy rates of CC 10 day protocol were similar to follitropin-alfa therapy.…”
Section: Discussionmentioning
confidence: 51%
“…This fact was men ti o ned be fo re in a num ber of stu di es. 11,12 Streh ler et al as ses sed 578 pa ti ents. 7 Tre atment with hu man me no po sal go na dot hro pin (hMG) was used in 282 pa ti ents, whe re as 296 pa tients we re tre a ted with r FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Ovaries of patients with PCOS are over-sensitive to the effects of FSH and therefore a low dose step-up protocol is recommented. 5,8 In our study, we aim to compare the treatment success and complication rates of clomiphene citrate (CC) and gonadotopins (r-FSH) using low dose step-up protocol, which are the two most frequently used ovulation induction agents in patients with polycystic ovary syndrome (PCOS).…”
Section: Comparison Of Clomiphene Citrate and Low Dose Recombinant Fsmentioning
confidence: 99%